Editorial: The Launch of Studies in Philosophy of Science and Education (SiPoSE) - Nadi Suprapto; Chih-Hsiung Ku; Tsung-Hui Cheng; Binar Kurnia Prahani (Indonesia Approach Education, 2020)
This small piece of the paper introduces the Studies in Philosophy of Science and Education (SiPoSE). As an international peer-reviewed journal, SiPoSE aware of the quality of the content. The rational, the purpose, and the scope are illustrated as the opening speech of the journal. Since the number of philosophy journals is still lacking in accommodating the ideas of philosophers in the world especially in the domain of science education and education in general, therefore, the existence of SiPoSE will fill the void of scientific discussion, especially in terms of Nature of Science (NOS), History of Science (HOS), Philosophy of Science (POS), and Philosophy of Education (POE).